2019
DOI: 10.21873/invivo.11763
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Podoplanin in Mammary Cancers in Female Dogs

Abstract: Background/Aim: Mammary neoplasms are very common tumours in female dogs. Cancer-associated fibroblasts (CAFs) play an important role in the oncogenesis process. One of the useful proteins used in the diagnostics of CAFs cells is podoplanin (PDPN). The aim of our study was to assess the expression of PDPN in mammary cancer in female dogs. Materials and Methods: Our study cohort included 61 cancers and 21 adenomas of the mammary tumour in bitches. Expression of podoplanin, Ki-67 and HER2 was determined using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…In the performed analyses, we showed a statistically positive correlation between the expression of POSTN and the expression of cell proliferation antigen Ki-67 in cancer cells in mammary cancer. The presented results are consistent with studies indicating a positive relationship between POSTN expression in cancer cells and the intensity of Ki-67 expression in breast cancer in women (38). The results of our research indicate that POSTN may be associated with the progression and increase of invasion of mammary glands in bitches.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the performed analyses, we showed a statistically positive correlation between the expression of POSTN and the expression of cell proliferation antigen Ki-67 in cancer cells in mammary cancer. The presented results are consistent with studies indicating a positive relationship between POSTN expression in cancer cells and the intensity of Ki-67 expression in breast cancer in women (38). The results of our research indicate that POSTN may be associated with the progression and increase of invasion of mammary glands in bitches.…”
Section: Discussionsupporting
confidence: 92%
“…One of the elements of the tumour stroma are cancerassociated fibroblast (CAFs) cells that play an important role in the process of carcinogenesis in humans (8,9,12). In our previous studies using IHC, podoplanin (PDPN) and POSTN expression in CAFs was found in mammary tumours in bitches (25,38). Morover POSTN expression at mRNA level was found in mammary tumours in female dogs (25,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…In canine mammary cancer, there is an increased expression of periostin in CAFs compared to mammary adenomas, and this has a positive correlation with the histological malignancy grade [85]. Similarly, the expression of podoplanin, a protein utilized to identify CAFs, showed a positive correlation with the histological malignancy grade in canine mammary cancer [82].…”
Section: Carcinogenesismentioning
confidence: 94%
“…Another element that participates in the process of carcinogenesis is cancer-associated fibroblasts (CAFs). These cells are part of the stroma and participate in the epithelialmesenchymal transition, secrete cytokines such as epidermal growth factor and transforming growth factor β and produce metalloproteinases that promote growth and tumor progression, invasiveness and metastasis [82][83][84]. In canine mammary cancer, there is an increased expression of periostin in CAFs compared to mammary adenomas, and this has a positive correlation with the histological malignancy grade [85].…”
Section: Carcinogenesismentioning
confidence: 99%